Fight for Religious Tolerance During the First Polish Interregnum (1572-1573) - Kornelia Wasiak (Codrul Cosminului, 2022)
As the Reformation progressed in the 16th century, Poland became increasingly populated by representatives of Protestant denominations. Because political elites and nobility disagreed on religious matters, the issue of religious tolerance required appropriate formal and legal solutions. That was particularly important during the first interregnum following the death of King Sigismund Augustus, when the spectre of anarchy loomed over the state. The Warsaw Confederation Act was introduced during the Convocation Sejm to preserve order in the country during the interregnum. This document also included provisions on religious tolerance, which remained a source of dispute for both supporters and opponents of religious peace for many years. This article addresses the first stage of the struggle for formal recognition of religious tolerance, which occurred between the death of the last monarch of the Jagiellonian dynasty (7 July 1572) and the end of the session of the Convocation Sejm during the first interregnum (28 January 1573). The study was built on 16th-century historiography - the works of Marcin Bielski, Świętosław Orzelski and Reinhold Heidenstein. The paper aims to reconstruct the events that led to the creation of the Warsaw Confederation Act. Moreover, the sources reflect the atmosphere prevailing in the country at that time, which is undoubtedly significant in capturing the topic under consideration. The paper is a three-part inquiry that, aside from research methodologies, displays the historical context in the introduction while the remainder of the text is a comparative analysis of the source material, from which relevant conclusions were drawn.